International Migration and the Integration of Labor Markets - Barry R. Chiswick; Timothy J. Hatton (Institute for the Study of Labor (IZA), 2002)
This paper is concerned with the determinants and consequences of intercontinental migration over the past four centuries. It begins with a review of the history of primarily trans-Atlantic migration to the New World during the period of Colonial settlement. The contract and coerced migration from Europe and Africa gave way, from the 18th century, to an era of free European migration. The period 1850 to 1913 was one of mass migration, primarily from Europe to North America and Oceania and from parts of Asia (primarily India, China and Japan) to other parts of Asia, Africa and the New World. World wars, immigration restrictions and the Great Depression resulted in a period of low international migration (1913 to 1945). In the post-World War II period international migration again increased sharply, but with changes in the nature of the flows, and under the constraints of immigration controls. Europe joined North America and Oceania as a major destination, as did the oil producing Arab countries bordering the Persian Gulf. The paper then explores the reasons for this international migration. Important factors include the relative wages in the origin and destination, the cost of international migration, the wealth to finance the investment, chain migration (kinship and information networks), as well as government subsidies to and restrictions on the free flow of people. The impact of international migration is explored in the context of a two-factor and a threefactor aggregate production function. Implications are developed for the aggregate (average) impact, as well as for the impact on the functional and personal distributions of income. The gainers and losers from international migration are considered. With insights on impact, a political economy approach is used to analyze the determinants of immigration controls. The influence on policy of gainers and losers from immigration was mediated by institutional change and by interest group politics. The long run relationship between globalization and international migration is explored.
Keywords: J31; J61; N30; 330; international migration; labor market integration; globalization; economic history; Internationale Wanderung; Migrationstheorie; Internationale Arbeitsmobilität; Reallohn; Arbeitsmarkt; Einwanderungsrecht; Welt